Handbook of tunnel fire safety - Beard, Alan; Carvel, Richard (ICE, 2012)
Following catastrophic fires that have occurred worldwide, it has become essential to gain a much better understanding of all aspects of tunnel fire safety, from basic science to acceptable risk and the law.